Disabling the Rhetoric of Prenatal Genetic Testing: A Critical Analysis of Online Pregnancy Self-Help Literature - Bakke, Abigail (Critical Disability Discourses, 2013)
Drawing on literature about the disability rights critique of prenatal genetic testing, this article consists of a critical analysis of a type of text in which socially-constructed negative attitudes about disability may be present: online pregnancy self-help literature about prenatal testing. The critique incorporates scholarship on the intersection of genetics and rhetoric in order to clarify rhetorical strategies used by writers of these online articles. The analysis shows that disability is rhetorically constructed as part of a tragedy narrative through negatively-connoted word choices and reductionist descriptions in the writing. Furthermore, the benefits of testing are construed as the ability of parents to treat or emotionally prepare for their child’s condition, as well as consider abortion, though the success of treatment and the possibility of abortion are masked or glossed over, giving parents an inaccurate picture of prenatal testing’s purpose and benefits. Keywords: pregnancy, genetics, prenatal testing, rhetorical analysis, disability rights critique